A Preliminary Test of the Interpersonal Psychological Theory of Suicidal Behavior in Young People With a First Episode of Psychosis. Issue 1 (13th October 2015) - Heelis, Rebecca; Graham, Hermine; Jackson, Chris
Abstract : Objectives: The interpersonal‐psychological theory (IPT) of suicidal behavior suggests that an individual who does not feel they belong and believes they are a burden combined with the capability to attempt suicide is more likely to attempt suicide. The study aimed to investigate this hypothesis in the context of psychosis. Method: Young people with a first episode of psychosis ( N = 45) who considered suicide, attempted suicide, and had no history of suicide or attempt were compared on self‐report measures of suicidal desire, capability for suicide, and substance use. Results: No significant differences were found between groups in terms of suicidal desire or capability. All participants perceived they were a burden, did not feel they belonged, and had the capability for suicide. Poisoning ( n = 22) was the most frequently reported method of a suicide attempt. Of those who had attempted suicide, 50% ( n = 7) reported that it had been related to a psychotic episode. Of the participants, 30 reported previous suicidal ideation mainly to completely end or stop the distress they were experiencing. Levels of depression were significantly different between groups; moderate levels of depression were reported in the suicidal ideation and attempt groups. Conclusion: The concepts of IPT appear to resonate with the experience of psychosis, regardless of suicidality. Specific features of psychosis and their influence on suicidality are worth further exploration.